Hubungan Ketaatan Beragama dengan Kecemasan Akademik Santri Pondok Pesantren Al- Hadi Girikusumo - Milawati, Malya; Sutoyo, Anwar (IAIN Kudus, 2022)
Relationship between Religious Obedience and Academic Anxiety of Al-Hadi Girikusumo Islamic Boarding School Students. The purpose of this study was to determine the relationship between religious observance and academic anxiety of the students of Al-Hadi Girikusumo Islamic Boarding School. This type of research is a descriptive correlational quantitative research. The population in this study were 346 MTs (Madrasah Tsanawiyah) students and 149 MA students (the sample was 149 MTs (Madrasah Tsanawiyah) students and 66 MA (Madrasah Aliyah) students who had high, medium, and low levels of religious obedience and academic anxiety. The sampling technique used was proportionate stratified random sampling. The data collection method used a religious obedience scale and academic anxiety scale. The validity test used the product moment formula and the reliability test used Cronbach alpha. The data analysis technique used was descriptive percentage data analysis and product correlation analysis. moment (pearson).The results of descriptive analysis show that the majority of the level of religious obedience of students are in the moderate category, namely (86.04%), then the academic anxiety level of the majority of students is in the medium category, which is equal to (75.3%).Furthermore, the results of the analysis correlation indicates that there is no relationship There is a very low correlation between religious obedience and academic anxiety in Al-Hadi Girikusumo Islamic Boarding School students with a very low degree of correlation (p = 0.675 > 0.05) and (r = -0.029) in the range of -0.00 to -0.199 degrees of correlation coefficient interpretation.Keywords: Religious Obedience, Academic Anxiety, Santri